The Economic Impacts of Tourism in Ouro Preto, MG, Brazil - Flecha, Angela Cabral; Fusco, José Paulo Alves [UNESP]; Damiani, Wagner Bronze; Amaral, Hudson Fernandes (My University, 2010)
The tourism spending like other activities has direct and secondary effects on the economy, and presents complex interaction with other activities deserving a special treatment for measuring its contribution to the global result of production and consumption. In this paper, it is used the Money Generation Model to measure the global economic impact of tourism sales in Ouro Preto, this method is not so limited by the data and it is able to produce good approximations to reality. It was not possible to adopt the WTO methodology due to data limitation. The results revealed the real importance of tourism for Ouro Preto, representing up to 10.4% of GDP in 2002, up to 21.8% of tax revenues in 2004, and approximately 11% of the region’s population in 2002 was related to tourism sales. Some actions can be outlined from these results in order to illustrate the current economic reality of the tourism in Ouro Preto. It is also possible to improve the tourist planning accomplished by the local City Hall in a coherent way with the economic results generated by the tourism.
Keywords: Economic impact of tourism; Money generation model; Multipliers; Ouro Preto – Brazil